Strengthening policies and structures to combat illicit tobacco trade in the Philippines - John Rafael Y. Arda; Alen Josef A. Santiago (Frontiers Media S.A., 2023)
The Philippines has been seeing an increase in illicit tobacco trade in recent years, undermining the impacts of legal measures such as tobacco products' taxation and regulation due to circumvention of established avenues and costing the government its revenue. Currently, the country has twelve policies related to the prevention of illicit tobacco trade with gaps identified in its lack of licensing systems for tobacco retailers and policies on law enforcement cooperation, which manifests in the country being fully compliant to only 5 of the 16 articles under the World Health Organization's Illicit Tobacco Trade Protocol. It is recommended that the country establish a national agency or framework specifically for illicit tobacco trade to address its gaps under Tracking and Tracing, Due Diligence, and Unlawful Conduct.